Pregnancy risks and contraceptive use among postpartum mothers in Cameroon: implications for improving the coverage of postpartum family planning services - Jean Christophe Fotso; John G. Cleland; Marquise Kouo Ngamby; Martina Lukong Baye; Elihouh O. Adje (BMC, 2023)
Plain Language Summary We use information from mothers with a child under the age of 18 months, who were interviewed in a national survey conducted in 2018. We examine risk of an unintended pregnancy, using data on factors that protect against risk, namely delayed resumption of sex and menses, breastfeeding and contraceptive use. Among mothers with an infant aged less than 6 months, very few were at risk mainly because they had not resumed sex. Among those with an infant aged 6-11 months, 26% had still not resumed sex and an equal proportion was partially protected by delayed resumption of menses. Only 17% were protected by use of a modern contraceptive method, leaving 24% fully at risk. Among those with a child aged 12-18 months, 30% were fully at risk. As expected, well educated, urban women were more likely to use contraception than less privileged women but less likely to be protected by delayed resumption of sex and menses, with the consequence that pregnancy-risk was similar. Though three-quarters of mothers had taken their child for vaccination on three or more occasions, only one-third had discussed family planning with a health provider at a visit to a facility in the previous 12 months. The need for improved contraceptive services for mothers with young children is clear. Short intervals between births are common in Cameroon and these threaten the health of mothers and children. It is equally clear that closer integration of family planning into mainstream health services is needed.